Determinacion sexual en Carica papaya L. - Thais Castro, L.=700 1 Ruiz, O.; Vielma, M.; Briceño R, A. de J.
(Es, En)
ilus., 12 ref.
Keywords: CARICA PAPAYA; ANATOMIA DE LA PLANTA; DETERMINACION DEL SEXO; MICROSCOPIA; LUZ; VENEZUELA